2008
DOI: 10.1007/s00425-008-0710-8
|View full text |Cite
|
Sign up to set email alerts
|

Auxin dynamics: the dazzling complexity of a small molecule’s message

Abstract: The phytohormone auxin is a potent regulator of plant development. Since its discovery in the beginning of the twentieth century many aspects of auxin biology have been extensively studied, ranging from biosynthesis and metabolism to the elucidation of molecular components of downstream signaling. With the identification of the F-box protein TIR1 as an auxin receptor a major breakthrough in understanding auxin signaling has been achieved and recent modeling approaches have shed light on the putative mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2009
2009
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 117 publications
(127 reference statements)
1
63
0
1
Order By: Relevance
“…Phenotypic variation in root growth was higher in response to the synthetic auxins naphthylacetic acid (NAA) and 2,4-D than to the natural auxin IAA ( Figures 1A-1C). This phenomenon is likely attributable to a slower removal via catabolization of the synthetic auxins, whereas a large excess of IAA is usually rapidly removed by conjugation to amino acids, sugars, or direct oxidation (Delker et al, 2008). High temperatures promote auxin-mediated hypocotyl elongation by increasing endogenous auxin contents Stavang et al, 2009).…”
Section: Natural Variation Of Physiological Auxin Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypic variation in root growth was higher in response to the synthetic auxins naphthylacetic acid (NAA) and 2,4-D than to the natural auxin IAA ( Figures 1A-1C). This phenomenon is likely attributable to a slower removal via catabolization of the synthetic auxins, whereas a large excess of IAA is usually rapidly removed by conjugation to amino acids, sugars, or direct oxidation (Delker et al, 2008). High temperatures promote auxin-mediated hypocotyl elongation by increasing endogenous auxin contents Stavang et al, 2009).…”
Section: Natural Variation Of Physiological Auxin Responsesmentioning
confidence: 99%
“…Auxin in particular is known to be a potent regulator of various aspects of plant development (Delker et al, 2008). At the cellular level, auxin responses are initiated by altering the expression of a multitude of genes, which requires the proteolytic degradation of transcriptional repressors by the 26S proteasome (Quint and Gray, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxin plays a fundamentally important role in polar growth of all organ primordia, including floral meristems (Cheng and Zhao, 2007;Benjamins and Scheres, 2008;Delker et al, 2008). Multiple mutants have been identified that fail to make flowers in Arabidopsis, resulting in a pin-shaped inflorescence phenotype (Bennett et al, 1995;Fig.…”
Section: Role Of Auxin In Axillary Meristem Initiation During Vegetatmentioning
confidence: 99%
“…For example, significant progress has been made charting the biosynthetic pathways by a combination of genetic and biochemical approaches, which revealed the operation of at least five different routes to IAA. Our current understanding of the redundant metabolic processes that determine auxin supply has recently been reviewed (Woodward and Bartel 2005;Delker et al 2008;Chandler 2009). The delivery of auxin from its biosynthetic sources to its sites of perception follows two major, unrelated modes of transportation: rapid longdistance movement via the phloem sap, and slower cell-to-cell distribution over shorter distances.…”
mentioning
confidence: 99%